Antibodies directed to antigens secreted by murine epithelioid macrophages modulate BCG-induced granulomata - Mario Mariano; Tania Aguiar; Celia R. W. Carneiro; Edilberto Postol; Venânclo A. F. Alves; Ricardo Ribeiro-dos-Santos (Mediators of Inflammation)
The authors have previously shown that epithelioid cells isolated from mice secrete a factor, called macrophage deactivating factor (MDF), that promptly deactivates superoxide release by activated macrophages and neutrophils. In this paper some biological properties of a polyclonal rat antiserum directed to MDF and other substances secreted by these cells are described. The immunoglobulin fraction of this antiserum reacted, by immunocytochemical methods, with epitopes in the cell membrane of macrophages adherent to coverslips subcutaneously implanted for 14 days; but not for 5 days. It also reacted with antigens within and outside cells in BCG-induced granulomas. This antiserum blocked completely the macrophage deactivating activity of epithelioid cell culture supernatants. Anti-IL-10 monoclonal antibody, did not block MDF activity. The administration of the immunoglobulin fraction from immunized rats to C5 deficient mice bearing BCG-induced granulomatas in the footpad, significantly reduced the size of the lesions. A marked necrosis of inflammatory cells and mononuclear cells phagocyting debris of necrotic cells were observed in these lesions.